Réponses

2012-05-28T22:26:34+02:00

tu remplace x par (-2/3)

(4x-3)²= ( (4*(-2/3)- 9/3)

           =(-8/3)-9/3)

           =(-17/3)²

           =289/9

(2x+7)= 2(-2/3)+7

          =-4/3 +7

           -28/21 + 21/21

           =-8/21

(4x-3)=

          (4(-2/3)-9/3)

           = -8/3  -9/3

           =-17/3

(2x+7)(4x-3)=-8/21 x -17/3

                   = 136/63

f(-2/3) =(289/9)+(163/63)

          (63/63)(289/9)+(9/9)(163/63)

             =(18207/567)+(1467/567)

              =19674/567

               = environ 34,7